2014
DOI: 10.1142/s1363919614500078
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Relationships Between Innovation Characteristics and It Innovation Adoption in Organisations: A Meta-Analysis Approach

Abstract: This paper presents the findings of a meta-analysis of innovation characteristics that influence the adoption of information technology (IT) in organisations. Past studies that examine the determinants of IT innovation adoption have produced inconsistent and contradictory results and deducing a definitive set of attributes for innovation adoption has become impractical. The study has aggregated findings of past research on IT adoption using meta-analysis to identify key factors in terms of innovation or techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 87 publications
1
33
0
Order By: Relevance
“…The small-sized healthcare provider's group showed their support to the TR than medium-sized health provider's group. The result contradicts a meta-analysis study [15] on relationship between organizational size and IT innovation adoption where they found that the larger the organization the more likely to be ready to adopt innovative due to their finical capacity and IT infrastructure advantages. However, this study is made on a developing country where the type of small healthcare providers are mostly from the private sector in which the financial resources can be more accessible to spend on new ways to provide a competitive and better quality health care.…”
Section: Discussionmentioning
confidence: 62%
“…The small-sized healthcare provider's group showed their support to the TR than medium-sized health provider's group. The result contradicts a meta-analysis study [15] on relationship between organizational size and IT innovation adoption where they found that the larger the organization the more likely to be ready to adopt innovative due to their finical capacity and IT infrastructure advantages. However, this study is made on a developing country where the type of small healthcare providers are mostly from the private sector in which the financial resources can be more accessible to spend on new ways to provide a competitive and better quality health care.…”
Section: Discussionmentioning
confidence: 62%
“…A four-stage model, including initiation, adoption, implementation, and routinization, was also examined (Vaidya, 2012). Although scholars split the IS implementation process into various stages, these models fit primarily into three phases, consistent with Rogers' (2010) model combining initiation, adoption and routinization stages (Hameed and Counsell, 2014). Similarly, IOS implementation can be seen as having three stages from a project management perspective: pre-adoption, adoption, and post-adoption (Zhu et al, 2006).…”
Section: Overview Of Iosmentioning
confidence: 99%
“…In particular, adopting innovative technologies such as Cloud computing technology could bring the benefits that are associated with it and offer economical and political legitimacy (Wang et al 2016) to the adoption. However, further analysis has revealed that tangible and intangible benefits such as increase of revenue, reduction of operational cost, increase of productivity, increase of efficiency of work processes, response time improvement, increased cash flow, competitive advantage, improved customer service, better relations with business partners and other opportunities are some of the major elements of relative advantage (Hameed andCounsell 2014, Premkumar et al 1994). Thus, the relative advantage has a none-arguable significant influence on the decision of adoption of Cloud computing (Hung et al 2010).…”
Section: Relative Advantagementioning
confidence: 99%
“…As per previous findings, the researcher believes that adoption of Cloud computing technology could bring some valuable benefits such as reduced operating costs, improved response time, improved productivity and provide a greater competitive advantage to the organization. Therefore, many studies suggested that relative advantage or perceived benefits as one of the top influencing factors to be considered to examine the Cloud adoption, and it could positively affect the Cloud adoption (Hameed and Counsell 2014).…”
Section: Relative Advantagementioning
confidence: 99%